If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-2a-5=3(5-2a)
We move all terms to the left:
-2a-5-(3(5-2a))=0
We add all the numbers together, and all the variables
-2a-(3(-2a+5))-5=0
We calculate terms in parentheses: -(3(-2a+5)), so:We get rid of parentheses
3(-2a+5)
We multiply parentheses
-6a+15
Back to the equation:
-(-6a+15)
-2a+6a-15-5=0
We add all the numbers together, and all the variables
4a-20=0
We move all terms containing a to the left, all other terms to the right
4a=20
a=20/4
a=5
| 3k+38=92 | | (60)+(4x)=90 | | 13–8x=141 | | 3(-2x+4)=-6x-12* | | 20=48t^2 | | 3s+4.75=21 | | 93/4−2s=21/4 | | x=74x≥13 | | 5=-1-7/k | | (4x+9)(5x+5)=180 | | 3(x+4)=-3* | | x^2-14x=287 | | 9x=135* | | 10(s-9)=-172 | | c/5c+5=30 | | x+4+x-5=90 | | -8x+8+3x-6=-3x+2 | | -8x+8+3x-6=-3x+2*4 | | -8-11x10=30 | | 7y+46=5(y+6) | | 2(3s+6)=60 | | -12x-15=-3(2x+3)* | | m+12=3m+4 | | -6(x-1)=-3-12 | | 4x-6=-5(x-6) | | 8x-3°=180° | | 22.5=x1.5 | | 1.5=x22.5 | | 104n+(-84n)=36 | | 16=5(v+4)-3v | | -4x+6(x-2)=-24 | | 4.75s+3=21 |